Overcoming Workplace Disability in IBD Patients: An Observational Study - Paulides, Emma (Inflamm Intest Dis, 2020)
BACKGROUND: Inflammatory Bowel Disease (IBD) can have considerable effects on employment outcomes because of its disabling character. GOALS: We aimed to investigate the impact of IBD in the workplace and to better understand the need for accommodations and adaptations. STUDY: Between November 2017 and March 2018, IBD patients were recruited from outpatient clinics in Christchurch Hospital, New Zealand. The survey assessed employment, the need for workplace accommodations and the difficulty arranging it, insurance, and disability using the item-reduced Inflammatory Bowel Disease Disability Index for self-report (IBD-DI-SR). Data were analyzed using descriptive statistics and multivariate logistic regression modeling. RESULTS: One hundred twenty-three patients were included (response rate 64%), 112 of whom reported that they experienced symptoms while working (60% female, 71% Crohn's disease, mean age 41.9 years). Ninety-one percent needed at least 1 workplace accommodation when symptoms were most severe. Almost half of the patients who needed an accommodation had difficulty arranging it. The most needed accommodations were time to go to medical appointments (71%) and easy access to a suitable toilet (71%). Being female, having less effective medication, and being distressed were associated with the need for 2 or more accommodations, difficulty in arranging accommodations, and not asking for needed accommodation. CONCLUSIONS: Many IBD patients need accommodations at work while symptomatic in order to overcome workplace disability, which can be difficult to arrange. Improved resources are needed to inform employees and employers about the disease, the possibilities for workplace accommodations, and practical strategies to request them.